PENGARUH RETURN ON ASSET (ROA), UKURAN PERUSAHAAN, LEVERAGE, PROPORSI DEWAN KOMISARIS INDEPENDEN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONDESIA TAHUN 2011-2015 - Muhammad Fauzan, 13.05.52.0112; Lisiantara, G. Anggana (Students Journal of Accounting and Banking, 2017)
This study examined the effect of the return on asset (ROA), company size, leverage, the proportion of independent commisioner board, and institutional ownership to the tax avoidance. This research was conducted at the Indonesian Stock Exchange by using analysis unit automotive and component that have gone public. The sampling method using purposive sampling the study period of 2011 to 2015. The relationship and influence between variables or described by using multiple regression analysis. The results showed that leverage and institusional ownership have significant positive effect to the tax avoidance. Company size has significant negative effect to the tax avoidance. Return on asset (ROA) and the proportion of independent commisioner board have non significant positive effect to the tax avoidance.Keywords: Return On Asset (ROA), Company Size, Leverage, The Proportion Of Independent Commisioner Board, Institutional Ownership, and Tax Avoidance